Primer for Developing a Farm Business Plan - Edward A. Evans (EDIS)
FE720, a 3-page fact sheet by Edward A. Evans, is the first of the Agribusiness Primer series, providing an overview of developing a business plan. It identifies the main components of a business plan and reiterates why you should develop one. Includes references. Published by the UF Department of Food and Resource Economics, August 2008.